The Dynamics of Semiconductor Laser under Optical Feedback - R. Ahmed, Abadhar (University of Thi-Qar Journal of Science, 2019)
The dynamical behavior of semiconductor laser in the present of optical feedback is studied by varying number of control parameters that appeared in the adopted theoretical model viz, linewidth enhancement factor , pump level , delay time and feedback level . Various dynamics seen to occur such as steady state, periodic, aperiodic and chaotic in the output of the semiconductor laser.